Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1101/204586
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magneto-active substrates for local mechanical stimulation of living cells

Abstract: 18Cells are able to sense and react to their physical environment by translating a mechanical cue 19 into an intracellular biochemical signal that triggers biological and mechanical responses.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…It could be shown that both the height of the pillars and the interpillar distance are important parameters to harmonize stability, actuatability, and cellular morphology within the whole cell analysis microsystem. It is convincing that this platform provides an advantageous and well‐defined way to study the mechanical stimulation of different cell entities on the single cell level 41. As a proof of concept, the early molecular responses of hMSCs to the external, magnetically driven mechanical stimuli were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…It could be shown that both the height of the pillars and the interpillar distance are important parameters to harmonize stability, actuatability, and cellular morphology within the whole cell analysis microsystem. It is convincing that this platform provides an advantageous and well‐defined way to study the mechanical stimulation of different cell entities on the single cell level 41. As a proof of concept, the early molecular responses of hMSCs to the external, magnetically driven mechanical stimuli were analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…[ 5 ] Such materials have potential uses in soft robotics and wearable technology, [ 6,7 ] and in drug delivery and other biological actuation applications due to the remote nature of magnetic fields. [ 8,9 ]…”
Section: Figurementioning
confidence: 99%
“…[ 2 ] Numerous studies have focused on replicating these morphologies and exploring artificial cilia for applications in microfluidic propulsion/mixing, [ 3–7 ] surface property modification, [ 8 ] enhancing catalytic reactions, [ 9,10 ] sensing, [ 11–14 ] microrobots/swimmers, [ 15,16 ] object transportation, [ 17–19 ] and cell stimulation. [ 20 ]…”
Section: Figurementioning
confidence: 99%